Synthesis and characterization of cellulose/polylactic acid/MnO2 bio-nanocomposite as a promising coating of paper sheet for food packaging application - Mahmoud E. Abd El-Aziz; Samir M.M. Morsi; Mohamed S. Hasanin; Ahmed M. Youssef (Carbohydrate Polymer Technologies and Applications)
Polymeric materials used in food packaging must possess unique mechanical, antibacterial, and permeability properties to successfully preserve the quality of food. Herein, a low-cost bio-nanocomposite film was coated on a paper sheet (PSH) for use in food packaging. The bio-nanocomposite film was based on cellulose nanocrystals (CNCs), polylactic acid (PLA), and MnO2 nanoparticles at different loadings (0, 1, 2, 3 wt % of PLA) to obtain CNCs/PLA, CNCs/PLA@1 %MnO2, CNCs/PLA@2 %MnO2, and CNCs/PLA@3 %MnO2, respectively. The crystallinity index of CNCs is 65 % using the Segal approach. The surface morphology of PSH, studied by scanning electron microscopy (SEM), showed a good distribution of MnO2 NPs in the bio-nanocomposite films, which in turn demonstrated good compatibility with PSH. The biodegradability increased by about 29 % in CNCs/PLA@3 %MnO2 due to the induced and induction effects of CNCs and MnO2-NPs as micronutrients, respectively. The water vapor transmission rate dropped from 890.34 in PSH to 145.46 g/m2.day in PSH coated by CNCs/PLA@3 %MnO2. Conversely, the oxygen transmission rate increased from 2.84 to 5.23 g/(m2.day). PSH coated with CNCs/PLA@2 %MnO2 showed the best tensile strength with an increase of about 147 %. The study presented a bio-nanocomposite coating that can be used to enhance packaging properties by preserving food during storage and preventing microbial growth.